Deep learning enhanced deciphering of brain activity maps for discovery of therapeutics for brain disorders - Xianrui Zhang; Zhen Liu; Xuan Luo; Yi Cao; Wencong Zhang; Honglin Li; Wei Li; Shuk Han Cheng; Stephen J. Haggarty; Xin Wang; Peng Shi (iScience, 2025)
Summary: This study presents an artificial intelligence enhanced in vivo screening platform, DeepBAM, which enables deep learning of large-scale whole brain activity maps (BAMs) from living, drug-responsive larval zebrafish for neuropharmacological prediction. Automated microfluidics and high-speed microscopy are utilized to achieve high-throughput in vivo phenotypic screening for generating the BAM library. Deep learning is applied to deconvolve the pharmacological information from the BAM library and to predict the therapeutical potential of non-clinical compounds without any prior information about the chemicals. For a validation set composed of blinded clinical neuro-drugs, several potent anti-Parkinson’s disease and anti-epileptic drugs are predicted with nearly 45% accuracy. The prediction capability of DeepBAM is further tested with a set of nonclinical compounds, revealing the pharmaceutical potential in 80% of the anti-epileptic and 36% of the anti-Parkinson predictions. These data support the notion of systems-level phenotyping in combination with machine learning to aid therapeutics discovery for brain disorders.